Periglaziale und rezente Verwitterung und Abtragung in den hessischen Basaltberglandschaften - Scharlau, Kurt (ERDKUNDE, 1953)
Many of the basalt rocks of the mountains of Hesse are covered with glassy layers „Schutzrinden (protective rinds) of leather-brown or reddish-brown colour which in that area could only have been formed during the last glacial period (Würm). It is possible to prove this by comparison with paleolithic artefacts since these show a patina due to the same causes, and it can be further confirmed by geomorphological investigations. The post-glacial weathering of a humid type leads, in contrast to the former conditions, to a bleaching of the rocks and destruction of these old protective rinds. These two processes of weathering which have contrary effects also provide a possible means of dating the basaltic „Blockmeere (boulder fields). Since they are made up of boulders which show these weathering rinds of the periglacial type they must date from the Würm period. These morphological features of periglacial type determine the present day landscape physiognomy, but their importance varies from place to place. Since the decline of the last glacial period (Würm) dissection and degradation working upon the rock waste, whose origin is due to periglacial soil creep, has been constantly increasing, in particular in the low-lying peripheral zones, whereas in the central mountain regions of higher altitudes the periglacial features still prevail. Nevertheless, even in these parts, they have been subject to some recent changes which are far from negligible. Amongst those of major importance is the removal by water of the „Feinerde (minute soil particles) from beneath the slopes of coarse basaltic rock waste. Related to this process is the haphazard change in the location of springs situated on the rock waste which has been termed „Vagabundieren (vagabondism). Shifts of soil matter during the recent past have resulted in transport of a considerable amount of material as a result of which fossil forms are being constantly changed. These processes and especially the changes in the quality of soil can be demonstrated by data taken from the historical geography of settlements.